A Study of Applying Sufficiency Economy to Lifestyles and use of Resources at Community Levels - Benjawan Ubonsri; Apaporn Pannun (My University, 2013)
This paper analyzes concept of Sufficiency Economy and how it can be applied to community development. Because of its flexibility and differences, applying the Sufficiency Economy principle depends on numerous community-related factors. The aim is examining the principle and studying how it poses physical, social and economic effects at community levels. This paper is also studying life change in accordance with the concept of Sufficiency Economy that determines the physical and socio-economic conditions in communities in order to define a policy that encourages community developments under Sufficiency Economy concept. This paper compares communal life change principles with three standard principles; that is, the principles by His Majesty the King, National Economic and Social Development Board (NESDB) and Bangkok Metropolitan, under the basic concept of Sufficiency Economy. The results are employed as Key Performance Indicators (KPIs) for pilot communities in Bangkok Metropolitan.
Keywords: Majesty; Social Economy; Standard of living; Fiscal Policy and Economic Growth